PREACHING BILL HIKMAH IN A PLURAL CONTEXT: STUDY OF JURGEN HABERMAS'S COMMUNICATION PARADIGM - Muhamad Abdul Manan; Mahmudi, Mahmudi; Muis, Abdul; Al Ghifari , Abudzar (Universitas Bondowoso, 2024)
This article explores the concept